Transient modeling of vapor compression refrigeration systems for domestic applications - Gardenghi, Álvaro Roberto (2020)
The increasing on energetic efficiency of household vapor compression refrigeration systems brings about a substantial impact in the energy consumption: about 17% of the overall electricity consumption worldwide is attributed to the refrigeration sector (including air-conditioning), being 45% the residential demand. A case study showing it is the Brazilian panorama, where such systems are responsible for approximately 27% of the residential electric consumption, representing about 8% of the whole country\'s demand. This issue is intensified due the low thermodynamic efficiency presented by these products. Therefore, industry and research institutes are dedicating increasingly efforts and time to develop and apply solutions to promote advances on systems\' operation. In this work, two mathematical models are presented: one based on a thermal analysis with the application of the first law of thermodynamics and other including the evaluation of the refrigerant mass distribution in the system. It is also developed an experimental procedure to calculate the thermal conductance and capacity of each component of a domestic refrigerator (compressor, condenser, capillary tube, evaporator, cabinet), which are necessary input data for the models. Experimental data describing the transient behavior of the refrigeration system are also obtained to validate the mathematical models. Two types of cabinets were studied: one with two compartments, operating with R134a and associated to constant speed and variable speed compressors; and a horizontal freezer, with one compartment and operating with R290. The simulation results follow the same experimental trends and are very satisfactory when compared to the transient and mean time experimental results. Two variable speed control strategies were evaluated, with gains up to 31% in consumption reduction by using them. An entropy generation analysis was performed for each system component and the overall system. Parametric analysis were conducted to identify the influence of ambient temperature, refrigerant charge and goods inside the compartments on the refrigeration system performance. The presented models are very appropriate for the transient simulation of vapor compression refrigeration systems for domestic applications.